Determination of Total Sulfur in Fertilizers by High Temperature Combustion: Single-Laboratory Validation. (27th November 2019) - Bernius, Jean; Kraus, Sabine; Hughes, Sandra; Margraf, Dominik; Bartos, James; Newlon, Natalie; Sieper, Hans-Peter
Abstract: A single-laboratory validation study was conducted for the determination of total sulfur (S) in a variety of common, inorganic fertilizers by combustion. The procedure involves conversion of S species into SO2 through combustion at 1150°C, absorption then desorption from a purge and trap column, followed by measurement by a thermal conductivity detector. Eleven different validation materials were selected for study, which included four commercial fertilizer products, five fertilizers from the Magruder Check Sample Program, one reagent grade product, and one certified organic reference material. S content ranged between 1.47 and 91% as sulfate, thiosulfate, and elemental and organically bound S. Determinations of check samples were performed on 3 different days with four replicates/day. Determinations for non-Magruder samples were performed on 2 different days. Recoveries ranged from 94.3 to 125.9%. ABS SL absolute SD among runs ranged from 0.038 to 0.487%. Based on the accuracy and precision demonstrated here, it is recommended that this method be collaboratively studied for the determination of total S in fertilizers.